2007
DOI: 10.1016/j.peptides.2007.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased hypothalamic angiotensin-(1–7) levels in rats with aortic coarctation-induced hypertension

Abstract: Since angiotensin (Ang) (1-7) injected into the brain blocked Ang II pressor actions in rats made hypertensive by aortic coarctation (CH), we examined systemic and tissue angiotensin peptide levels, specifically concentrating on the hypothalamic Ang-(1-7) levels. Plasma, heart and kidney isolated from CH rats showed increased levels of Ang I, Ang II and Ang-(1-7) compared with the normotensive group, with Ang II being the predominant peptide in heart and kidney. In the hypothalamus, equimolar amounts of Ang II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
16
0
2
Order By: Relevance
“…It has been reported that blockade of endogenous Ang-(1–7) by microinjection of A-779 into the PVN reduces renal sympathetic tone in normal rats [30]. Ang-(1–7) level in hypothalamus is increased in aortic coarctation-induced hypertensive rats [31]. However, it is not known whether Ang-(1–7) in the PVN is involved in the excessive sympathetic activation and the enhanced CSAR in hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that blockade of endogenous Ang-(1–7) by microinjection of A-779 into the PVN reduces renal sympathetic tone in normal rats [30]. Ang-(1–7) level in hypothalamus is increased in aortic coarctation-induced hypertensive rats [31]. However, it is not known whether Ang-(1–7) in the PVN is involved in the excessive sympathetic activation and the enhanced CSAR in hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…This primary response occurs as a consequence of reduced renal perfusion and subsequent activation of the renin-angiotensin system during the first week of coarctation (10). Furthermore, we previously showed that cardiac and plasma levels of angiotensin II (Ang II) were increased in this renovascular model of hypertension (11), and several studies have demonstrated that aortic coarctation in rats caused cardiac hypertrophy at 2, 6, and 28 days after ligation of the abdominal aorta (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Aortic coarctation is a renovascular model of hypertension that depends on angiotensin II function [46] . In this model, we previously showed a redox imbalance in the aorta [9] , heart [8] and kidney [21] and oxidative stress generation that contributed in the development of the hypertensive stage.…”
Section: Discussionmentioning
confidence: 99%